Fluoride Concentration in Children’s Toothpaste and Mouthwash sold in Bogota, Colombia (Revista Nacional de Odontología, 2016)
Introduction: Toothpaste and mouthwash are obviously the most used means of fluoride application by the general population. Objective: To determine fluoride concentrations in toothpaste and mouthwash for children sold in the supermarkets of Bogota, Colombia, and to verify if said values are consistent with the values informed by the manufacturer.Material and Methods: 17 toothpastes and 4 mouthwashes were evaluated. The total amount of fluoride (ft) and of ionic fluoride (fi) was evaluated; and in the toothpaste that contained sodium monofluorophosphate, the total soluble fluoride (fst) was also evaluated. The fi was evaluated in all mouthwash. A specific fluoride electrode was used attached to an ion analyzer, previously calibrated with fluoride standards after adding tisab ii as buffer solutions. A descriptive statistical analysis was performed.Results: 18% of toothpastes presented values between 12, 5 and 13, 9% under the amount expected for ft. One toothpaste presented 77% offi values under the expected amount, which was the same in fst values of 48, 7% underneath the expected. One of the mouthwash received a fi value of 7% above the expected.Conclusion: Most of the studied toothpastes and mouthwash presented values of ft and fi according to the information given by their manufacturers. However, inconsistencies were found in the fluoride concentration in some products, which may affect their anti-cavity effect
Keywords: Colombia; toothpaste; mouthwash; fluoride; children; security